Breastfeeding practices and lactation mastitis in Western Nepal: A prospective cohort study - Khanal, Vishnu (Curtin University, 2016)
A sample of 735 mothers was recruited in Western Nepal and interviewed regularly for 6 months. All mothers initially breastfed their infants, with 42.2% initiating within the first hour after birth. However 30.6% introduced prelacteal feeds before initiating breastfeeding. Exclusive breastfeeding rates were 66.3% at one month and 39.2% at four months. The incidence of lactation mastitis was 8.0% during the neonatal period. More than 99% of infants were still receiving breastmilk at six months.